Ordinal methods: Concepts, applications, new developments, and challenges-In memory of Karsten Keller (1961-2022) - Amigó, Jose Maria (2023)
During the 10 years since then, the new “ordinal” methodologyhas been intensively further developed by theoreticians and practitionersin different directions. However, many of the new conceptsand approaches are still not fully understood and there is also aneed for a more systematic application of ordinal methods. For thisreason, Karsten Keller and the two of us decided to guest edit thisFocus Issue of Chaos on Ordinal Methods: Concepts, Applications,New Developments and Challenges, where researchers from differentdisciplines could report on recent advances in the Bandt and Pompemethodology, thus making possible the exchange of new ideas andsynergies.